PHILOSOPHICAL INSIGHT INTO FUTURE METALLURGY IN THE CONTEXT OF DIGITAL TRANSFORMATION (Web of Technology: Multidimensional Research Journal, 2025)
One of the fundamental principles of the 21st century is that the process of digital transformation penetrates deep into all spheres. The metallurgical sector is no exception. Digital technologies, artificial intelligence, automated control systems, cyber-physical complexes are revolutionizing the process of metal production. This article treats on the development of metallurgy in the era of digital transformation, its socio-spiritual impact and philosophical conclusions about the future.